How fast is it? : a zippy book all about speed - Hillman, Ben, 1957- (New York : Scholastic, 2008)
1. Speed--Juvenile literature
Includes index.
Basic ed. students
Keywords: Speed -- Juvenile literature; Speed; Velocity; Physics